Trophoblast-induced spiral artery remodelling and uteroplacental haemodynamics in pregnant rats with increased blood pressure induced by heme oxygenase inhibition. (1st January 2020) - Oltra, L.; Reverte, V.; Garcés, B.; Li Volti, G.; Moreno, J.M.; Salazar, F.J.; Llinás, M.T.
Abstract: Introduction: The aim of the present study was to determine the contribution of the heme oxygenase (HO) system to the adaptation of the uteroplacental circulation to pregnancy in the rat, and its relationship with the maintenance of blood pressure during late gestation. Methods: The HO inhibitor, stannous mesoporphyrin (SnMP), or vehicle were administered intraperitoneally to virgin and midpregnant rats. Mean arterial pressure (MAP) was measured before and after the treatment, in the conscious rats. Uterine and radial arteries blood flow velocities were obtained from pregnant rats at days 14 and 19 of gestation using high frequency ultrasonography. Trophoblast invasion and spiral arteries remodelling were analyzed in the mesometrial triangle of pregnant rats by immunohistochemistry. Results: HO activity inhibition during late gestation induced a significantly increase in the MAP of pregnant rats (114 ± 1 mmHg vs 100 ± 2 mmHg, p < 0.05) but it did not affect this parameter in virgin rats (121 ± 2 mmHg vs 124 ± 3 mmHg). MAP elevation was associated with marked (p < 0.05) decreases in the systolic and diastolic flow velocities in uterine and radial arteries, as compared with pregnant control rats. Furthermore, spiral arteries of pregnant rats treated with SnMP showed lower (p < 0.001) proportion of lumen circumference covered by trophoblast (21 ± 3%) and a higher (p < 0.05) proportion of vascular smooth muscle (33 ± 5%) than control pregnant rats (59 ± 5% and 16 ± 5%, respectively) Discussion: These data indicate that HO system play an important role in the adaptation of the uteroplacental circulation to pregnancy and in the blood pressure regulation during late gestation. Highlights: Heme oxygenase activity inhibition during pregnancy induces hypertension. Uteroplacental haemodynamics is altered by reductions in heme oxygenase activity. Heme oxygenase activity inhibition induces defective spiral arteries remodelling.